Representasi Toxic Positivity dalam Anime Takopi's Original Sin (Perspektif Roland Barthes) - Nikita, Moira; Sari, Wulan Purnama (Kiwari, 2025)
Anime serves as a medium that can portray social behavior while communicating cultural values to its audience. This study examines the representation of toxic positivity and its connection to trauma in Takopi’s Original Sin using Roland Barthes’ semiotics. The analysis draws on social construction theory, interpersonal communication, and mass communication to understand how emotional norms are formed and reproduced through visual narratives. A qualitative approach is applied through Barthes’ semiotic method, supported by scene documentation and interviews with a psychology lecturer to validate the interpretation. The findings show that toxic positivity appears through verbal and nonverbal signs such as forced smiles, repeated positive statements, and physical gestures used to suppress or conceal negative emotions. Through the layers of denotation, connotation, and myth, these signs reveal how characters internalize social expectations to appear stable despite experiencing emotional pressure. The analysis also shows that traumatic experiences shape how the characters respond to conflict, making the optimism they display function more as a coping mechanism. Overall, the study concludes that toxic positivity in Takopi’s Original Sin is portrayed as an emotional pattern shaped by social pressure, unhealthy relational dynamics, and the characters’ inability to process negative experiences. Anime menjadi media yang mampu menggambarkan perilaku sosial sekaligus menyampaikan nilai budaya kepada penonton. Penelitian ini menganalisis representasi toxic positivity dan kaitannya dengan trauma dalam Takopi’s Original Sin dengan menggunakan semiotika Roland Barthes. Penelitian mengacu pada teori konstruksi sosial, komunikasi interpersonal, dan komunikasi massa untuk melihat bagaimana norma emosional dibentuk dan direproduksi melalui narasi visual. Pendekatan kualitatif diterapkan melalui teknik analisis semiotika Barthes, didukung dokumentasi adegan dan wawancara dengan dosen psikologi sebagai validasi interpretasi. Hasil penelitian menunjukkan bahwa toxic positivity muncul melalui tanda verbal dan nonverbal seperti senyum yang dipaksakan, ucapan positif yang diulang, serta gestur fisik yang digunakan untuk menahan atau menutupi emosi negatif. Melalui lapisan denotasi, konotasi, dan mitos, tanda-tanda tersebut memperlihatkan bagaimana karakter mengingat tuntutan sosial untuk terlihat stabil meski sedang tertekan. Analisis juga memperlihatkan bahwa pengalaman traumatis membentuk cara tokoh merespons konflik, sehingga optimisme yang mereka tampilkan lebih berfungsi sebagai mekanisme bertahan. Secara keseluruhan, penelitian ini menyimpulkan bahwa toxic positivity dalam Takopi’s Original Sin direpresentasikan sebagai pola emosional yang terbentuk oleh tekanan sosial, dinamika hubungan yang tidak sehat, dan ketidakmampuan karakter memproses pengalaman negatif.